Oceanic Lithosphere 3. The Origin and Evolution of Oceanic Lithosphere: The Geochemistry and Origin of Oceanic Lavas - Robinson, Paul; Malpas, John (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1999)
Summary Oceanic lavas are the most voluminous volcanic products on Earth. Between 15 and 20 km 3 of new oceanic crust is created every year by eruption of mid-ocean ridge basalt (MORB) along sea-floor spreading axes. MORB lavas areolivine- and hypersthene-normative tholeiites highly depleted in incompatible trace elements such as Rb, Sr, Ba,K, Zr, Y and the light rare earth elements. Isotopically, they are characterised by low radiogenic Sr and Pb and high radiogenic Nd. They are formed by decompressional melting of shallow mantle material as it rises beneath spreading axes. This upper mantle source was previously depleted in incompatible elements by extraction of continental crustal material early in Earth history. On a global scale MORB lavas are remarkably uniform, but relatively enriched varieties (E-MORB) are known from all ridge segments. These enriched lavas are transitional in composition to ocean island basalts (OIB) which have much higher contents of incompatible elements and much more varied isotopic compositions than typical MORB lavas. Ocean island basalts are believed to form by partial melting of mantle plumes that rise from near the core-mantle boundary. These plumes entrain mantle material that has been relatively enriched by recycled crustal materials in subduction zones. Mixing of plume mantle and depleted MORB mantle on a variety of scales can explain the occurrence of E-MORB lavas. Large-scale super plumes are believed to be responsible for the formation of oceanic plateaus, which are built by voluminous eruptions of ocean island basalts.